Accidents on Farms. Case Analysis - Gaweł, Wanda; Maczewska-Borny, Iwona; Poławska, Małgorzata (Ubezpieczenia w Rolnictwie – Materiały i Studia, 2024)
Farm work involves numerous hazards that can lead to accidents or occupational diseases, often representing a tragedy for families and, for the farm itself, a loss that is difficult to compensate. The aim of this article is to analyse the causes and circumstances of accidents occurring during farm work. An accident in agricultural work must simultaneously meet three conditions: it must be sudden, have an external cause, and be connected with the performance of agricultural work, while the absence of any of these criteria means that the incident cannot be recognised as an agricultural work accident. The article also addresses the issue of essential work performed during sick leave, during which a farmer may suffer an accident, and the most common reasons for refusing a one-off compensation payment in connection with an accident on a farm are also discussed. The preventive measures undertaken by the Agricultural Social Insurance Fund (KRUS, the Fund) aim to reduce the number of agricultural work accidents and minimise risks that may lead to such incidents. The article presents an analysis of accidents on farms, methods of preventing accidents, and rules for ensuring safety during work, and also highlights the primary causes of accidents within specific groups. A case analysis was utilised as a research method in this article.